The Concept of STAD (Student Team Achievement Division) Cooperative Learning Model According to Robert E. Slavin: Konsep Model Pembelajaran Kooperatif STAD (Student Team Achivement Devision) Menurut Robert E. Slavin - Isnaini, Firdha; Kurniawan, Machful Indra (Indonesian Journal of Education Methods Development, 2020)
Education is an important aspect of preparing human resources as a means of national development. The success of education in improving human resources is not from teachers' role in developing student abilities. Professional teachers are required to have skills, skills in which pedagogic skills are one of the skills of a quality classroom teacher. One of the factors that affect the quality of teacher learning is the learning model. According to Robert Slavin, this study aims to describe the concept of the STAD type cooperative learning model and the relevance of the STAD type cooperative learning model to the process skills of elementary school students. The research method uses the method of literature study or literature study. The results showed that the concept of the STAD type cooperative learning model according to Slavin is a learning model carried out through small groups consisting of 4 to 5 students in a group or team, where each team or group consists of heterogeneous students (various types of different) such as gender, ability, ethnicity and race, and each group has a tutor as a student in carrying out group learning. Furthermore, the results show that its relevance to elementary school students' skills shows that the STAD type cooperative learning model (student team achievement division) can develop elementary school student process skills, where the discussion process carried out by students through quizzes involves students actively in higher-order thinking activities. It shows that the STAD cooperative learning model (student team achievement division) is very relevant for developing the skills of elementary school students